The importance of the pharmaceutical patient questionnaire from the coordinated care perspective - Jurewicz, Błażej; Oberska, Joanna; Prusaczyk , Artur; Żuk, Paweł; Guzek, Marika; Bogdan, Magdalena (Journal of Education, Health and Sport, 2022)
In the pharmaceutical care the pharmacist cooperates with other representatives of the medical professions and caters the patient with holistic care. The pharmacist concentrates on identifying and solving drug problems. The tool that makes the process feasible is the pharmaceutical patient questionnaire. Introducing this pharmaceutical patient questionnaire is the main goal of the paper. This research investigates the issue of defining and creating pharmaceutical patient questionnaire, which can be used in coordinated pharmaceutical care process. The paper shows an original concept created by Medical and Diagnostical Center in Siedlce, Poland (MCD). In the research and analysis process the authors of the study have created an original concept of pharmaceutical patient questionnaire, which can be used in coordinated pharmaceutical care process in Poland. The pharmaceutical patient questionnaire comprises the following information: patient’s personal data, patient’s subjective feelings concerning his health, different illnesses, allergies, vaccinations, preventive medical examinations and other basic medical indicators or parameters. At the core of the pharmaceutical patient questionnaire is the information on the type of medicine used taken by the patient, the name of the medicine, the doses, effectiveness of the therapy, side effects and own patient’s medicine supplies. This tool also comprises information on pharmacist- patient interview, the pharmacist’s recommendation and other concerning information. Identification and reinforcement of the scope of information provided in the frame of pharmaceutical patient questionnairemay have a crucial influence on implementing and conducting coordinated pharmaceutical care.